The impact of biliary stents on the diagnostic yield of endoscopic ultrasound‐guided fine needle aspiration for solid pancreatic lesions: A single‐center retrospective study and meta‐analysis - Go Endo; Kazunaga Ishigaki; Tsuyoshi Hamada; Yousuke Nakai; Kota Ishida; Kohei Kurihara; Shuichi Tange; Shinya Takaoka; Yurie Tokito; Yukari Suzuki; Hiroki Oyama; Sachiko Kanai; et al. (DEN Open)
Abstract Background Endoscopic ultrasound‐guided fine needle aspiration (EUS‐FNA) is widely used for the pathological diagnosis of solid pancreatic lesions but in cases with obstructive jaundice, transpapillary sampling can be performed during endoscopic retrograde cholangiopancreatography with transpapillary biliary stent placement. Thus, it is still controversial whether EUS‐FNA should be performed prior to endoscopic retrograde cholangiopancreatography with biliary stent placement or only after negative transpapillary sampling. Methods The accuracy, sensitivity, and specificity of EUS‐FNA for solid pancreatic lesions with or without indwelling biliary stents were retrospectively studied in patients undergoing EUS‐FNA between January 2017 and December 2021. We also conducted a meta‐analysis including our data to compare the accuracy and sensitivity of EUS‐FNA with or without biliary stents. Results A total of 509 patients (40 with biliary stents and 469 without biliary stents) were included. The accuracy (77.5% vs. 94.5%, p < 0.001) and sensitivity (71.0% vs. 91.7%, p < 0.001) were lower in EUS‐FNA with biliary stents. A meta‐analysis confirmed that accuracy (odds ratio [OR] of 0.43, 95% confidence interval [CI] 0.29–0.62, p < 0.001) and sensitivity (OR of 0.46, 95% CI 0.33–0.64, p < 0.001) were lower in EUS‐FNA with biliary stents. There were no statistically significant differences between plastic stents and self‐expandable metallic stents for accuracy or sensitivity. Conclusions The presence of biliary stents had a negative impact on the diagnostic performance of EUS‐FNA, and EUS‐FNA prior to endoscopic retrograde cholangiopancreatography with biliary stent placement should be considered in cases with obstructive jaundice.